Analisis Keandalan Sistem Distribusi Tenaga Listrik Akibat Gangguan pada Masa Pandemi COVID-19Di PT. PLN (Persero) ULP Sidareja - Wawan Setiawan; Randi Adzin Murdiantoro; Nasrulloh Nasrulloh (Program Studi Teknik Elektro Universitas Peradaban, 2021)
Electricity is the energy that is very needed by the society, mainly during the Covid-19 pandemic in now era, people are often stay at home because of PSBB (Large-Scale Social Restrictions), WFH (Work From Home) and online schools. Therefore, PLN is required to maintain the quality of electrical energy that is distributed to the customers. An electric power distribution system can be said to be reliable is if the disturbances and blackouts that occur in a certain period of time are below the specified reliability index number. A measure of the reliability in a system can be stated by calculating the SAIFI (System Average Interruption Frequency Index) and SAIDI (System Average Interruption Duration Index). The electric power distribution system in ULP Sidareja has a SAIFI value of 0,179 times/customer/year and SAIDI value of 0,199 hours/customer/year. The SAIFI and SAIDI value in ULP Sidareja is still below of the standard value which set by the SPLN 68-2-1986 standard, IEEE std 1366-2003 and WCS, furthemore the quality of the electricity distribution system in ULP Sidareja can be categorized as reliable.